From Peer Education to Legal Empowerment: Youth-Led Strategies for Preventing Sexual Violence in Indonesia - Anis Widyawati; Lyna Latifah; Shofriya Qonitatin Abidah; Heru Setyanto; Lulus Rahma Putra (The Indonesian Journal of International Clinical Legal Education, 2025)
Sexual violence against minors in Indonesia remains a critical issue that reflects deep structural inequalities and limited protective mechanisms. This study applies a normative juridical approach, drawing on statutory law, ministerial regulations, case reports, and scholarly commentary to examine how legal and community-based strategies intersect in addressing the problem. The method relies on secondary data rather than field research, with analysis focused on interpreting how legal frameworks connect with peer education and adolescent mentoring initiatives. The results point to three central gaps: the lack of a comprehensive sexuality curriculum in schools, limited recognition of bodily autonomy, and weak integration of prevention programs into existing legal structures. These shortcomings create vulnerabilities that leave young people without adequate tools to protect themselves or seek help. The discussion highlights four interrelated strategies to strengthen adolescent resilience: preparing trained peer educators, establishing structured mentoring and counseling systems, involving families and community organizations, and implementing targeted public-awareness campaigns. Each element contributes to both community-level support and the realisation of statutory obligations to protect children from sexual violence. Although this research does not provide empirical measurements, its interpretive analysis outlines a framework that may guide future studies and inform policymakers. By connecting legal obligations with practical community efforts, the study underscores that peer education and mentoring are not peripheral solutions but integral components of a rights-based approach to safeguarding adolescents.